Should New Zealand Shirk Its Obligations? A Critical Perspective on Private Law Scholarship - Marten, Bevan; McLay, Geoff (Victoria University of Wellington Law Review, 2016)
This article concerns the role of the private law scholar in New Zealand, and how such scholars use their skills to improve the law. It argues that while an obligations scholar’s preference may be to engage with the courts and other academics in their scholarly activities, a focus on statutory reform better suits New Zealand conditions. Scholars should share their talents with policy makers, law reform bodies and legislators, helping to explain the importance of a coherent system of private law, and how this may be achieved. The authors then go a step further by suggesting that, in the New Zealand context, the preferable approach to reform may be one involving policy-based solutions exemplified by the accident compensation scheme, as opposed to approaches based on traditional private law principles such as party autonomy.